Wybrane cechy rozwoju języka u dzieci z niepełnosprawnością wzroku - Kucharczyk, Izabella (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
This review of research literature presents the difﬁculties encountered by blind children at individual developmental stages of speech. This report aims to appraise recent peer reviewed literature relating to communication and language development in children with VI. The language and communication developmental characteristics may assist speech-language therapists to build a knowledge base for parti- cipation in early intervention for young children with visual impairment.